Environmental Assessment of Heavy Metal Pollution around Industrial Area in Southwestern, Nigeria - Ibrahim, Kehinde Olojoku; Orosun, Muyiwa Michael; Purchase, Megan Welman; Yusuf, Mumeen Adebayo (Journal of Sustainable Natural Resources, 2024)
This study investigated the heavy metals contamination around industrial district in Southwest Nigeria. The study region lies between latitudes 7° 54 and 7° 56 and longitudes 6° 24 and 6° 27. Thirty (30) samples of groundwater, thirty (30) samples of soil, and twelve (12) samples of plants were collected from the study area. All samples were collected in triplicate. Physical and chemical parameters were examined in groundwater, soil, and plant samples. The average pH level in groundwater samples is 7.2 which falls within the Nigerian Standards for Drinking Water Quality (NSDWQ). The ranges of the other physical parameters (Ec, TDS, and TH) are also within the acceptable limits. The mean concentrations of heavy metals (HMs) in groundwater samples are Mn (0.020mg/l), Zn (0.010mg/l), Ni (0.010mg/l), Cr (0.130mg/l), Cu (0.020mg/l), and Fe (0.090mg/l) with the exception of Pb (0.090mg/l) that above the recommended level. According to the index of geo-accumulation (Igeo), soil and plant samples are not polluted with respect to the heavy metals tested. The analysis of the human risk assessment of HMs reveals that the values for the carcinogenic risk are within acceptable bounds, however the values for the non-carcinogenic risk are substantially above acceptable bounds. This demonstrates that non-carcinogenic health impacts are a threat to the broader population. This study suggests continuous monitoring of groundwater, soil, and plant in the study area.